Structural health monitoring of the church of Santa Casa da Misericórdia of Aveiro using FBG sensors - Lima, Hugo F.
This paper presents a structural health monitoring system for monitoring, with reduced visual impact, one historical building structural. The system is based on fiber Bragg gratings and comprises 19 displacement sensors and 5 temperature sensors. All the sensors were custom made according to the monitoring points' characteristics. The results obtained over the first year of monitoring are presented. The objective of this work is to gather data that will bring a deeper knowledge of how this structure behaves and to help planning the recovering interventions in this historical building.